Reentry of Incarcerated Juveniles: Correctional Education as a Turning Point Across Juvenile and Adult Facilities - Jäggi, Lena (Criminal justice and behavior, 2020)
All incarcerated juveniles have to receive correctional education, but little is known about how these school experiences influence reentry. With longitudinal data of 569 incarcerated juveniles (91% male) from the Pathways to Desistance Project, this study tested how motivational (teacher bonding, school orientation, time spent on homework) and performance (grades) aspects of schooling were related to desistance for youth returning from juvenile versus adult facilities. Results revealed that across facility type, increased attachment to facility schools, but not grades, predicted increased gainful activity (attending school and/or working), less self-reported delinquency, and lower recidivism in the community. Path models showed that gainful activity during Months 1 through 6 was related to stay in community, but not to self-reported behavior in Months 7 through 12. Results indicate that incarceration is an environment that shapes future behavior, but also highlight differences between behavioral and system responses. Facility school experiences might be an important locus of intervention.